Basic data for Elevated plasma phospholipid n-3 docosapentaenoic acid concentrations during hibernation (PONE-D-22-30692R2) - Strandvik, Birgitta (Karolinska Institutet, 2023)
This data was used in a study investigating plasma phospholipid fatty acid profiles during hibernation and summer in free-ranging brown bears (Ursus arctos) and in captive garden dormice (Eliomys quercinus). The data shows elevated plasma phospholipid n-3 docosapentaenoic acid concentrations.

An analysis of blood samples from bears and dormice.

Blood samples were taken from 11 free-ranging sub-adult 2-to 3-yr-old Eurasian brown bears equipped with a Global Positioning System (GPS) collar in Dalarna and Gävleborg´s Counties, Sweden during 2012-2014.

In total 56 garden dormice obtained from a breeding colony kept at the Research Institute of Wildlife Ecology (Vienna, Austria) were included in these experiments. The dormice presented in this study were part of a large experiment conducted over 3 consecutive years where animals had to be sacrificed at different time-points during hibernation (torpor and euthermic) to assess to various tissues, including the heart and other organs of interest.

A variable lists with descriptions for each table are included in the documentation files

Förhöjd koncentration av n-3 docosahexaenoic syra under hibernering hos två djurarter.

Fettsyreanalyse av blodprover från björn och möss
Data för Elevated plasma phospholipid n-3 docosapentaenoic syra koncentration under hibernering hos två djurarter (PONE-D-22-30692R2)
Elevated plasma phospholipid n-3 docosapentaenoic acid concentrations during hibernation
Keywords: zoology; zoologi; Brown Bear; brunbjörn; hibernation, fatty acids; hibernering, fettsyror; Trädgårdssovare; Ursus arctos; Eliomys quercinus; Garden Dormouse; Zoology; Zoologi; Molecular Biology; Molekylärbiologi